The most excellent and lamentable tragedy of Romeo & Juliet - Hinds, Gareth, 1971-; Shakespeare, William, 1564-1616. (Somerville, Mass. : Candlewick Press, 2013)
A graphic novel adaptation of William Shakespeare's classic tragedy about Romeo Montague and Juliet Capulet, two young people whose love for one another is doomed by the long-standing feud between their families, with characters recast as multiracial individuals.
Comic book adaptation of Romeo and Juliet / William Shakespeare.
Spine title: Romeo & Juliet.
School Library Journal, November 2013
Horn Book Starred, November 2013
Library Media Connection starred, March 2014
Kirkus Starred, September 2013
Keywords: Romeo -- (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Juliet -- (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Vendetta -- Comic books, strips, etc. -- Juvenile fiction; Man-woman relationships -- Comic books, strips, etc. -- Juvenile fiction; Verona (Italy) -- Comic books, strips, etc. -- Juvenile fiction; Romeo -- (Fictitious character) -- Fiction; Juliet -- (Fictitious character) -- Fiction; Vendetta -- Fiction; Man-woman relationships -- Fiction; Verona (Italy) -- Fiction; Romeo -- (Fictitious character) -- Comic books, strips, etc. -- Fiction; Juliet -- (Fictitious character) -- Comic books, strips, etc. -- Fiction; Vendetta -- Comic books, strips, etc. -- Fiction; Man-woman relationship -- Comic books, strips, etc. -- Fiction; Verona (Italy) -- Comic books, strips, etc. -- Fiction; Comics adaptations; Graphic novels